Chemical control of pilea microphylla in euterpe oleraceae nurseries with oxyfluorfen - Romani, G. N. [UNESP]; Queiroz, J. R G [UNESP]; Silva, M. T. [UNESP]; Alves, P. L C A [UNESP]; Pivetta, K. F L [UNESP] (My University, 2013)
The açai palm is a Brazilian native species and economically important, grown for the hearts of palm and fruit extraction, as well as the seedling production for ornamental purposes. The weed control is one of the concerns observed in seedling production, which has the artillery plant (Pilea microphylla) with the major and widespread occurrence. Thus, the aim of this trial was to evaluate the selectivity and efficacy of oxyfluorfen in artillery plant control in açai (Euterpe oleracea) seedlings. The experimental design was completely randomized. The treatments were arranged in a 2 x 3 factorial scheme, using 2 types of herbicide application: broadcast spraying (sprayed over total area) and spot spraying (directed to the target) and 3 oxyfluorfen dosages (0, 72 and 144 g of active ingredient ha-1) with four replications. Each experimental unit consisted by one açai palm pot infested by artillery plant. They ere visually evaluated for seedling toxicity and the weed control percentage, at 7, 15, 30, 45 and 60 days after application (DAA). There was 100% control of artillery plant from 15 to 60 DAA for the two tested dosages, regardless of application type. However, 100% control was observed at 7 days, using 1.5 L ha-1 in the spot type. The effects of phytotoxicity from 30 to 60 days was moderate, regardless the application method or dosage.
Keywords: Açai palm; Artillery plant; Palm heart; Seedlings; Weed chemical control